2020
DOI: 10.1039/c9ee02795e
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity thermochemical CO2 dissociation using iron-poor ferrites

Abstract: Dissociation of CO2 to form CO can play a key role in decarbonizing our energy system. Fe-poor ferrites exhibit significantly higher capacity for thermochemical CO2 dissociation than state-of-the-art materials such as ceria and perovskites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…S1–S2, Table S1, and Subsections 1–4 in Supplementary Text of ESI†). The thermodynamic requirements for reactions (1)/(3) and (4) to proceed are: 51 where p O2 is the (equivalent) oxygen partial pressure during thermal or chemical reduction and…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1–S2, Table S1, and Subsections 1–4 in Supplementary Text of ESI†). The thermodynamic requirements for reactions (1)/(3) and (4) to proceed are: 51 where p O2 is the (equivalent) oxygen partial pressure during thermal or chemical reduction and…”
Section: Resultsmentioning
confidence: 99%
“…1C and D can still give a relatively accurate estimation of thermodynamic equilibrium CO 2 splitting capacity, as often seen in published van't Hoff analyses. 44,51 In general, for a material whose dots are dense in the thermodynamically feasible zone, its h O and s O properties remain feasible for the two-step cycle across a large range of x , leading to a large thermodynamic equilibrium CO 2 splitting capacity. The density of dots between 1 and 4 and between 2 and 3 is higher for Fe 0.45 Co 0.55 O x 1 than for Fe 2/3 Co 1/3 O x 2 , and therefore, Fe 0.45 Co 0.55 O x 1 has a higher oxygen exchange capacity because of a larger range of x , giving a larger total entropy of reduction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that La 0.6 Sr 0.4 MnO 3‐ δ perovskites have a critical CO 2 :CO conversion ratio of 650:1 at T red = 1300 °C and p O 2 = 10 −5 atm, and T oxi = 800 °C indicating a very low conversion extent and using a lower CO 2 molar gas flow rate than critical (CO 2 :CO) ratio would result in negligible or zero CO yield. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%